VD_FINDINFO HC / 2012 / 15 vom 20. Dezember 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, DIVORCE, CONJOINT, ENFANT, MAJORITÉ{ÂGE} | 125 al. 1 CC, 125 CC, 276 al. 1 CC, 276 CC, 279 al. 1 CC, 279 CC